Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Manajemen Laba - Rafrafi Zul Abrari; Agus Sihono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The term "profit management" refers to managerial practices that manipulate financial statement data to make a good impression on stakeholders. This approach can help businesses by improving their reputation, but due to the lack of transparency, it is detrimental to stakeholders and the public. The purpose of this study is to evaluate empirically how profitability, leverage and company size affect profit management. Using the purposive sampling technique, this study selects 18 food and beverage sub-sector businesses listed on the Indonesia Stock Exchange from 2019 to 2024. Multiple linear regression is used in statistical software to test the secondary data of the annual report. The findings of this study indicate that profit management is simultaneously influenced by profitability, leverage, and firm size. Partially, profitability and firm size are not indicated to affect profit management, while leverage has been shown to have a significant positive influence on profit management.